2016
DOI: 10.1007/s13311-016-0451-5
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and the Silent Sequelae of Stroke

Abstract: Depression and fatigue are common after stroke and negatively impact the quality of life of stroke survivors. The biological bases of these symptoms are unknown, but an abundance of data point to a role for inflammation. This review highlights evidence supporting the contribution of inflammation to poststroke depression and poststroke fatigue. Potential treatments for poststroke depression and poststroke fatigue are explored, with a special emphasis on those that modulate the immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 135 publications
1
27
0
Order By: Relevance
“…[103][104][105] These studies are quite small, however, and larger studies controlling for baseline comorbidities and stroke characteristics are needed to adequately address the relationship between C-reactive protein and PSF.…”
Section: Inflammation Immune Response and Genesmentioning
confidence: 99%
“…[103][104][105] These studies are quite small, however, and larger studies controlling for baseline comorbidities and stroke characteristics are needed to adequately address the relationship between C-reactive protein and PSF.…”
Section: Inflammation Immune Response and Genesmentioning
confidence: 99%
“…[21][22][23] Therefore, immune system-mediated inflammation is critically involved in determining the fate of the brain following ischemic stroke. [24][25][26] Understanding the mechanisms underlying role of neuroinflammation in ischemic stroke would provide important targets for the development of therapy in ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…In general, elevations in circulating pro-inflammatory cytokines such as IL-1β, TNF-α, and IL-6 have been linked to larger infarct size and worse prognosis, while the opposite is true for circulating levels of anti-inflammatory cytokines like IL-10 and IL-1RA [69,84]. Becker [27] indicated that overall systemic milieu after stroke, rather than a single cytokine or other biological substrate that cause either PSD or PSF. Despite evidence that stroke induces systemic inflammation and sickness behavior-like symptoms, few studies have examined the association between stroke-induced inflammation and PSF or PSD.…”
Section: Post-stroke Fatigue and Depressionmentioning
confidence: 99%